Rational and Emotional Communication in Advertising in Women's Magazines in Brazil - Edward Robinson Marin; Nadia Kassouf Pizzinatto; Antonio Carlos Giuliani (BBR: Brazilian Business Review)
This article investigated the incidence of rational and emotional arguments in messages from 5.536 advertisements of six women's magazines in Brazil (Claudia, Nova, Estilo, Marie Claire, Elle and Gloss), published between May / 2008 and August / 2009. The methodology was based on an exploratory study, supported on a scale of 14 items, by Resnik and Stern (1977), which recommend matching appeals to attitude toward the product, that is, use informative advertising, based on rational appeals for products in which the consumer attitude is predominantly cognitive. To assess the emotional content, we used the scale of eight items of Plutchik (1980), represented by the primary emotions - Anger, Fear, Sadness, Disgust, Surprise, Curiosity, Acceptance and Joy. Data analysis included the frequency of the two appeals in the general category (durables, non-durables and services), product, and correspondence analyzes were used to identify the prevalence of two types of arguments in selected magazines. The results show the concentration of ads on non-durable goods, followed by the category of services, that overcomes the advertisings on durables. The study also analyzes the incidence of emotional and rational arguments by product category and by magazine.